Here's Looking at You, Kid: Nonhuman and Human Privacy Entanglements in the Surveillant Assemblage - Langstone, Delia (Privacy Studies Journal, 2026)
This paper explores the routine collection of data from animals and the ramifications of privacy for human and nonhuman animals. There is an unprecedented incursion into the lives of nonhuman animals that have never been more “visible” as new “smart” surveillance technologies are pushed by the impetus of surveillance capitalism. There are various biometric technologies such as Facial Recognition AI, neural networks looking for emotions in “abnormal” goats, happy cows, and grimacing pigs, pet microchips, activity trackers for dogs, animal identification tracking in the food chain, and myriad technologies for observing and tracking wildlife. Surveillance implies unequal power relations since it is “embedded into asymmetric social relationships,”1 a postulation which is especially true when it involves nonhuman animals, adding particular issues to an examination of privacy. Critical privacy debates tend to be human-centred, however, this examination argues for a multisensorial notion of privacy when it applies to animals, drawing on Solove’s ideas to reconfigure the notion of privacy for animals. It is taken from a wider study of animal surveillance drawing on empirical case studies examining the implications for human and nonhuman animals of some of the latest technologies for scrutiny that are an emerging dynamic in the Surveillant Assemblage. 1 Christian Fuchs, ”How Can Surveillance Be Defined? Remarks on Theoretical Foundations,” in The Internet & Surveillance - Research Paper Series, edited by the Unified Theory of Information Research Group, 2010, 9.